2014
DOI: 10.1016/j.ejvs.2014.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results from a Prospective Study of Laparoscopic Aortobifemoral Bypass Using a Clampless and Sutureless Aortic Anastomotic Technique

Abstract: EVREST greatly facilitates laparoscopic aortic surgery in occlusive disease with no need for suture or clamping of the aorta. This technique performed in a single center on 12 patients, seems to be feasible and safe. It offers the advantages of laparoscopy and those of endovascular surgery, especially in the challenging conditions encountered during aortic laparoscopic surgery. Early experience supports procedural and initial postprocedural safety and demonstrates proof-of-concept for EVREST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The technique was faster than the conventional suture technique and after 30 days had a similar tensile strength. This may open the use of this technique in complex debranching procedures, totally telescoped grafts and even facilitating the laparoscopic aortic anastomosis [ 10 ] . New hybrid devices may be developed for these applications.…”
Section: Resultsmentioning
confidence: 99%
“…The technique was faster than the conventional suture technique and after 30 days had a similar tensile strength. This may open the use of this technique in complex debranching procedures, totally telescoped grafts and even facilitating the laparoscopic aortic anastomosis [ 10 ] . New hybrid devices may be developed for these applications.…”
Section: Resultsmentioning
confidence: 99%
“…In 2008, Lachat et al 12 introduced the Viabahn Open Revascularization TEChnique (VORTEC), in which a stent graft is used to form a sutureless anastomosis in renal revascularization surgery. Since then, several authors (Bonvini et al, 13 Segers et al, 14,15 Donas et al, 16 Papadimitriou et al 17 ) have attempted to use this technique in aortic surgery. According to this technique, the aorta is punctured and a guidewire is positioned in the aorta.…”
Section: Aad Typesmentioning
confidence: 99%
“…devices during open surgery, whereas five studies [13][14][15][16][17] reported a laparoscopic approach. Only two studies 34,45 reported comparative results of postoperative outcomes for hand-sewn anastomosis vs AADs.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%
“…3 Papadimitriou et al 4 reported the use of a sutureless anastomosis in 6 patients with calcified aortas, using a stent-graft telescoped into the infrarenal aorta and partly deployed within and partly outside the aorta as a bridge between the target artery and the Dacron graft. Recently, Segers et al 5 described a similar sutureless anastomosis technique in a calcified infrarenal aorta using a laparoscopic approach. Compared with the approach we used, these techniques have the advantage of avoiding surgical suture; however, in order to obtain good seal of the endograft, at least 2 cm of overlap are required into the native aorta and 2 cm into the Dacron graft.…”
Section: Journal Of Endovascular Therapy 22(2)mentioning
confidence: 99%